Housing First/HUD-VASH. Issue 7 (July 2015) - Westermeyer, Joseph; Lee, Kathryn; y Carr, Tegan Batres
<x xml:space="preserve">Abstract</x> Abstract This paper consists of responses to issues raised in the accompanying Commentary. Our response is organized under three topics: (1) reasons regarding the importance of issues, (2) the need for a comprehensive framework in housing placement, and (3) conceptualization and scientific design (with details on contemporary methods for investigating unanticipated consequences when randomization is no longer feasible). Recurrences to substance use disorder in the American Society of Addiction Medicine (ASAM) housing placement condition are noted within hours or days, with rapid implementation of planned contingencies, and avoidance of enabling. Recurrences in the Housing First/HUD-VASH (HF/H-V) condition escape notice for weeks to months, and continued use is accepted as a core principle of the program. HF/H-V contingencies occur later for major disruptions, leading to discharge. For patients recruited from our clinic, HF/H-V performed poorly when compared to a long-accepted standard of care, the ASAM placement criteria.